Effect of aging treatment on fracture toughness in ZM61 magnesium alloy. (March 2015) - Yu, D. L.; Zhang, D. F.; Zhao, D. Z.; Hu, G. S.; Pan, F. S.
<x content-type="archive" xml:space="preserve">Abstract</x> The effect of aging treatment on fracture toughness in Mg–6Zn–1Mn (wt-%) was investigated by optical microscopy, scanning electron microscopy, transmission electron microscopy, scanning transmission electron microscopy, uniaxial tensile and fracture toughness tests, respectively. The results showed that the fracture toughness of Mg–6Zn–1Mn alloy can be enhanced by aging treatment. The fracture toughness and strength showed a reverse trend in single aged and double aged alloy. Synergetic effect of fine grains and precipitates improved the fracture toughness more sharply than aging treatment. The precipitate free zones and grain boundary precipitates made the largest contribution to the reduction of toughness. Under as extruded and aged conditions, the main origins of cracks were elastic incompatibility and plastic deformation.